2017
DOI: 10.1007/s41825-017-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

Whatever happened to the Golden Age of natural gas?

Abstract: Recent technology innovation in the natural gas industry has powered a shale gas boom, enabling the narrative that natural gas is a transition fuel to a low-carbon future. However, this narrative has not manifested itself uniformly around the world and, more fundamentally, it must be tested and revised periodically to reflect rapidly changing market, supply chain, and environmental realities. The growth in production has put downward pressure on prices, incentivized increased consumption and trade in the comin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In 2011, China's gas demand totalled 108.9 billion cubic metres (bcm) and the IEA's GAS scenario expected that it would reach 247 bcm by 2015; in fact, total demand that year was 194.7 bcm. At the time, there was concern that China's gas demand was stagnating and that a Golden Age of Gas seemed unlikely (Boersma and Jordaan 2017). Then, stimulated by Government targets, demand grew rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, China's gas demand totalled 108.9 billion cubic metres (bcm) and the IEA's GAS scenario expected that it would reach 247 bcm by 2015; in fact, total demand that year was 194.7 bcm. At the time, there was concern that China's gas demand was stagnating and that a Golden Age of Gas seemed unlikely (Boersma and Jordaan 2017). Then, stimulated by Government targets, demand grew rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…25 For definitions of the IGU regions see Appendix 3. 26 For comments on the IEA's Golden Age of Gas hypothesis see: IEA WEO (2017, Box 1, p. 337); Stern (2017);and Boersma and Jordaan (2017). 27 Three of the five scenarios in the Annual Energy Outlook presentation (Slide 27) by the EIA Administrator Sieminski (2017) in January 2017 suggested that prices will be at or below $5/MMbtu until 2040.…”
Section: Evolution Of Wholesale Gas Prices In Different Regionsmentioning
confidence: 99%
“…In addition, the unknowledgeable group decision may reflect the perception amongst citizens that Qatar's natural gas resource is a major economic engine and source of government funding so it should be preferable over other resources. A number of recent studies have also highlighted the potential of natural gas to reduce anthropogenic carbon dioxide in the near term and to act as a transitional fuel to renewable fuels [63,64]. However, a long-term dependence on this form of energy may stymie the transition to green energy sources [65].…”
mentioning
confidence: 99%